Forensic Science in the Elementary Classroom - Todd Campbell; Brianna Worst (Networks: An Online Journal for Teacher Research, 2005)
This article stems from a pre-service teacher's attempt to translate "inquiry as a theory" into "inquiry as a practice" in a science classroom. It is intended to provide a snapshot of grappling with inquiry instruction, from both a pre-service teacher and a science teacher educator's perspective, while also offering approaches for allowing students to engage in scientific inquiry by posing questions and working toward solutions. Lastly, this article offers what the teacher researcher and the teacher educator learned in the pre-service preparation program.